RNA-seq analyses of the midgut from blood- and serum-fed Ixodes ricinus ticks - Perner, Jan; Provazník, Jan; Schrenková, Jana; Urbanová, Veronika; Ribeiro, José M C; Kopáček, Petr (Scientific reports, 2016)
Adult females of the genus Ixodes imbibe blood meals exceeding about 100 times their own weight within 7‒9 days. During this period, ticks internalise components of host blood by endocytic digest cells that line the tick midgut epithelium. Using RNA-seq, we aimed to characterise the midgut transcriptome composition in adult Ixodes ricinus females during early and late phase of engorgement. To address specific adaptations to the haemoglobin-rich diet, we compared the midgut transcriptomes of genetically homogenous female siblings fed either bovine blood or haemoglobin-depleted serum. We noted that tick gut transcriptomes are subject to substantial temporal-dependent expression changes between day 3 and day 8 of feeding. In contrast, the number of transcripts significantly affected by the presence or absence of host red blood cells was low. Transcripts relevant to the processes associated with blood-meal digestion were analysed and involvement of selected encoded proteins in the tick midgut physiology discussed. A total of 7215 novel sequences from I. ricinus were deposited in public databases as an additional outcome of this study. Our results broaden the current knowledge of tick digestive system and may lead to the discovery of potential molecular targets for efficient tick control.
Keywords: Cattle; Animals; skot; sekvenční analýza RNA; Intestines; transkriptom; střeva; Ixodes; Female; zvířata; Transcriptome; klíště; Sequence Analysis, RNA; Gene Expression Profiling; ženské pohlaví; stanovení celkové genové exprese